Hadith #2557 - Sunan Abi Dawud - Abdullah bin al-Jahm عبد الله بن الجهم الرازي; Ahmed bin Abi Sarayj أحمد بن أبي سريج; Amr bin Abi Qays عمرو بن أبي قيس الرازي الأزرق كوفي; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
It has been prohibited to ride the beast which eats dung.
Grade: Sahih